Income risk vulnerability and perception towards conservation: a community level analysis for Pulau Sibu -Tinggi Marine Park, Mersing - Fatimah, K; NurulHuda, M.S; Salleh, N.H.M (University Kebangsaan Malaysia, 2012)
This paper seeks to examine the trade-off between conservation and the incidence of poverty among the marine park community in the Sibu-Tinggi Marine Park, Mersing, Malaysia. The aim of this study is to look at the magnitude of income variation (vulnerability) as environmental constraints are imposed and determine the factors that may mitigate such risk exposure in the community. This study enables policy makers to formulate better marine diversity conservation policies through the designation of marine parks.The fundamental question is how variation in income (across households and across alternative incomes) represents the revenue instability that may affect the sustainability of the community’s daily livelihood. In light of mandatory marine park regulations, the community will be deprived of basic access to marine resources within 2 nautical miles of the nearest shoreline. In addition, the tourism sector may provide an alternative income option which may be lucrative enough to supplement their existing livelihoods. Nevertheless, the inability to gain access to capital and marketing channels will impede these opportunities as physical and financial infrastructure remain lacking and under provided for. Given such constraints, will the community be able to adapt to marine park regulations and if they do, what are the costs they have to pay?